Direct electroseparation of zinc from zinc sulfide in eco-friendly deep eutectic solvent: Highlighting the role of malonic acid - Wang, Zhiwei; Zhang, Zhenya; Yuan, Tian; Shimizu, Kazuya; Wang, Ding; Luo, Daijiang; Wang, Daoxiang; Ru, Juanjian (Separation and purification technology, 2023)
•Zn is directly separated from ZnS in choline chloride-urea-malonic acid (ChCl-urea-MA) deep eutectic solvent.•This process achieves the current efficiency of 86.5 % with the energy consumption of 2621.8 kW·h·t−1.•MA causes 0.13 mol·L-1 ZnS being dissolved to form stable MA-based ligands.•This study initiatively simplifies Zn separation from ZnS in green solution with hazardous waste minimization. Zinc sulfide (ZnS), one of the main ingredients of zinc ore and emerging materials, partly processes environmental risk. Deep eutectic solvents (DESs) are green solvents to efficiently separate metals with less emission. In this study, a novel route for direct electroseparation of Zn from ZnS in eco-friendly choline chloride-urea DES with the addition of malonic acid (MA) is studied for the first time. The role of MA and the reduction behavior of Zn(II) are systematically analyzed by cyclic voltammetry. The reduction of Zn(II) is quasi-reversible and follows one-step two-electron transfer process. Pure Zn with nanostructure is obtained with the current efficiency of 86.5 % and energy consumption of 2621.8 kW·h·t−1 at the optimized parameters of 10 mA·cm−2, 353 K and 100 mM·L-1 ZnS. Mechanisms analyses indicate that in the presence of 60 mM·L-1 MA, besides [ZnCl−3]- and [ZnCl−5]3-, some ZnS are dissolved to form stable [Zn(MA)2-Cl−2]4-, [Zn(MA)2-Cl-]3- and other MA based ligands, which causes a higher Zn ion solubility of 0.13 mol·L-1 and may promote the subsequent electroseparation of ZnS. Results from this study are expected to propose a simplified route to directly separate Zn from ZnS without oxidation pretreatment to achieve hazardous waste minimization.